Price Distortion in the Indonesia’s Tobacco Market: An Islamic Economic Ethics Perspective - Abd Aziz (Masyrif : Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
Tobacco is one of the strategic agricultural sectors that supports the economy of rural communities in Indonesia. Although it contributes significantly to farmers' income, tobacco pricing practices at the upstream level are still dominated by an oligopsonistic market structure, placing farmers in the weakest position. This study aims to explain the causes of tobacco price distortions and review them through the lens of Islamic economic ethics. This research uses the library research method by reviewing classical and contemporary literature on prices, justice, market mechanisms, and the works of scholars such as Ibn Taimiyah and al-Ghazali. The results show that price distortion occurs due to quality standards determined unilaterally by manufacturers, farmers' lack of access to information, economic dependence on companies, and a closed trading system. This situation is not in line with the principles of justice, transparency, and prohibition of exploitation in Islamic economics. Ibn Taymiyyah's perspective emphasizes that fair prices should follow the mechanism of supply and demand without intervention that harms either party, while al-Ghazali emphasizes the importance of market supervision to maintain public welfare. Thus, this study confirms that the application of Islamic ethical values in the tobacco distribution chain is important for building a more transparent, fair, and beneficial market for farmers.